Cognitive skills programs for female offenders in the community: effect on reconviction - Palmer, Emma J. (Criminal justice and behavior, 2015)
This article reports an evaluation of two cognitive skills programs (Enhanced Thinking Skills and Think First) with 801 women offenders serving community sentences in the English and Welsh Probation Service. A quasi-experimental design was used to compare the reconviction rates at 1-year follow-up of offenders who completed the program, offenders who started but did not complete the program, and a comparison group that were not allocated to the program. Multivariate analysis showed that the completers did not have a significantly lower rate of reconviction than the comparison group. However, the non-completers had a significantly higher rate of reconviction than the comparison group. No differences were found in reconviction between the completers group and non-completers group. The implications of the findings for interventions with women offenders are discussed.